2000
DOI: 10.1038/sj.ejhg.5200438
|View full text |Cite
|
Sign up to set email alerts
|

Predictive testing for hereditary breast and ovarian cancer: a psychological framework for pre-test counselling

Abstract: Since the identification of two breast-ovarian cancer susceptibility genes (BRCA1/2), predictive testing for hereditary breast/ovarian cancer (HBOC) has been available. Given the complexity and uncertainties of HBOC and the potential impact of predictive testing on psychological well-being, we offer the test applicants a combination of information-oriented and psychological counselling. In this paper, we describe the multidisciplinary approach for predictive testing for HBOC as a clinical service in Leuven, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Associations between genetic causal beliefs and reactions to personal genetic test results have previously been explored (Cameron et al 2009;Decruyenaere et al 2000;Marteau and Weinman 2006), but with the exception of one focus group study examining interest in genetic testing for obesity among obese adults (Segal et al 2007a), the present study is the first that we are aware of to examine the association between genetic causal beliefs and interest in personal genomic information upstream in the genomic feedback process in an unselected patient population. We previously reported that the majority of participants in this study believed that genetics influences all four diseases "some" to "a lot" (Sanderson et al 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Associations between genetic causal beliefs and reactions to personal genetic test results have previously been explored (Cameron et al 2009;Decruyenaere et al 2000;Marteau and Weinman 2006), but with the exception of one focus group study examining interest in genetic testing for obesity among obese adults (Segal et al 2007a), the present study is the first that we are aware of to examine the association between genetic causal beliefs and interest in personal genomic information upstream in the genomic feedback process in an unselected patient population. We previously reported that the majority of participants in this study believed that genetics influences all four diseases "some" to "a lot" (Sanderson et al 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Since the introduction of genetic testing for HBOC in the mid-1990s, psycho-social research on the potential impact of genetic testing has been primarily focussed on attitudes and components of decision-making before undergoing testing [5, 6, 7, 8, 9, 10]and on distress and adjustment to test results [11, 12, 13]. Family communication of HBOC test results and the willingness of those family members who have had a diagnosis to inform other members has been more recently addressed by Julian-Reynier et al [14, 15], Wagner Costalas et al [16], Hughes et al [17]and Claes et al [18].…”
Section: Discussionmentioning
confidence: 99%
“…In some countries, family cancer clinics offer professional psychosocial support to asymptomatic women from HBOC families (61,62). However, more data are needed to determine: 1) how much and what type of information and support (both pre-and posttesting) are required for those offered genetic testing and how this can be most efficiently provided and 2) how to achieve better understanding of genetic testing and its results, and how one can best facilitate risk-reducing behavior without high levels of emotional distress or false reassurance (4).…”
Section: Psychological Support Needsmentioning
confidence: 99%